A representação da informação em prontuários de pacientes de hospitais universitários: uma análise à luz da teoria comunicativa da terminologia - Silva, Josiane Cristina da [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Information Science develops methodologies for processing, accessing and transferring information and knowledge, in view of the needs and demands of users and establish relations with the Terminology, because when considering the function of organizing information and knowledge, both fulfill the role of retrieving and disseminating information and serve users in their informational needs. It is also noteworthy that, among the many possibilities of interdisciplinary studies in the field of Information Science, information in health care is of great importance. Although information has a core value in contemporary society, in health, scientific-technical information is vital. In this work, information in health care refers to the study of health care terminology, pointing out that the technical and scientific terms in this field are mainly used for reporting information and transferring of knowledge among professionals. However, the variation in the terminology of health care requires technical and scientific terms harmonized, since they show a lot of imprecision and ambiguity and can hinder the retrieval of information by health care professionals. Taking into consideration the need to use a more harmonious terminology, for better communication among health care professionals, emerged the proposal to highlight the importance of the Communicative Theory of Terminology through an analysis of the representation of information in medical records of patients from university hospitals, specifically in the Neurology field. It was observed in the comparison made among University Hospitals, namely, the Clinical Hospital at the Faculty of Medicine of Marília and the Clinical Hospital at the Faculty of Medicine of Ribeirao Preto, University of Sao Paulo that there are more similarities than differences at filling out patient records. As to the... (Complete abstract click electronic access below)

A Ciência da Informação desenvolve metodologias para tratamento, acesso e transferência da informação e do conhecimento, tendo em vista as necessidades e demandas dos usuários e estabelece relações com a Terminologia, pois ao considerar a função de organização da informação e do conhecimento, ambas cumprem os papéis de recuperar e disseminar a informação e atender os usuários em suas necessidades informacionais. Ressalta-se ainda, que dentre as inúmeras possibilidades de estudos interdisciplinares no campo da Ciência da Informação, a informação em saúde é de grande importância. Pois embora a informação tenha um valor essencial na sociedade contemporânea, na área da saúde, a informação técnica-científica é vital. Neste trabalho a informação em saúde referese ao estudo da terminologia da área da saúde, destacando-se que os termos técnico-científicos desse campo do saber são utilizados principalmente para a comunicação de informações e transferência de conhecimentos entre os profissionais. Todavia, a variação na terminologia utilizada na área da saúde requer a harmonização dos termos técnico-científicos, visto que estes apresentam imprecisão e ambiguidade e podem dificultar a recuperação da informação pelos profissionais. Considerando-se ser necessário o emprego de uma terminologia mais harmoniosa para uma melhor comunicação entre os profissionais de saúde surgiu a proposta de se destacar a importância da Teoria Comunicativa da Terminologia através de uma análise da representação da informação em prontuários de pacientes de hospitais universitários, especificamente na especialidade Neurologia. Observou-se, na comparação feita entre os Hospitais Universitários, a saber, o Hospital das Clínicas da Faculdade de Medicina de Marília e o Hospital das Clínicas da Faculdade de...
Keywords: Ciência da informação; Sistemas de recuperação da informação; Saúde pública; Arquivos medicos; Hospitais universitarios; Representação do conhecimento (Teoria da informação); Teoria comunicativa da terminologia; Prontuários de pacientes; Information Science; Terminology; Medical records of patients; Communicative Theory of Terminology; Health Care Information